2018
DOI: 10.3390/economies6030047
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology in the Role of Information System of Healthcare Facility in the Slovak Republic

Abstract: Abstract:The study presents a general overview of the healthcare facility system of the Slovak Republic, especially in a field of the innovation process of the management information system, with a purpose of analysing the consistency and a unity of the system. The data applied in this analysis is collected as a part of the Gesiti research project. This project is developed for mapping out the management of an information system and information technology in healthcare facilities around the whole world. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Lack of discussion about this topic can be seen in society-wide discussions and public interests, as well as at the level of scientific and professional discourses [Gavurová et al, 2018]. There are no research teams in scientific workplaces that address this topic; moreover, no Slovak universities teach this subject, and, so far, the issue of science communication has not appeared in national grant schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of discussion about this topic can be seen in society-wide discussions and public interests, as well as at the level of scientific and professional discourses [Gavurová et al, 2018]. There are no research teams in scientific workplaces that address this topic; moreover, no Slovak universities teach this subject, and, so far, the issue of science communication has not appeared in national grant schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted concerning the effective use of HRIS in the health sector (Gavurová, Balloni, Tarhaničová, & Kováč, 2018). Miller's (2021) study proposed the introduction of appropriate policies for the sustainability of the health sector using HRIS.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…According to Ibrahim and Daneshvar [59], reduction in health expenditure does not necessarily reduce efficiency of health care system if the operational and technical aspects are improved. Another study [60] reported that information and communication technologies can improve the level of health care services. Stefko et al [61] identified and quantified the impact of medical technologies (magnetic resonance devices, computed tomography devices) on the efficiency of the health care facilities.…”
Section: Introductionmentioning
confidence: 99%